A Iniciativa Botsu: Promovendo a Educação em Robótica e Sustentabilidade por Meio do Lixo Reciclável - JOSÉ VIEIRA DOS SANTOS NETO (2024)
Amid everyday demands, robotics emerges as a crucial tool to simplify human life, especially in the context of early childhood education in sustainable and smart cities, a growing trend. However, in the Brazilian educational scenario, the acquisition of resources, both physical and logical, for teaching robotics represents a substantial challenge. Additionally, the lack of training of basic education teachers in Brazil in robotics intensifies this challenge. Given this panorama, this work aims to develop the initial version of a web platform called Botsu. This platform aims to provide, through videos and tutorials, a step-by-step guide for creating robotic prototypes aimed at simulations in classrooms, addressing solutions to real problems in cities and using sustainable materials. Purpose goes beyond conventional learning; Botsu is expected to become a valuable ally in teaching, enabling children to not only absorb knowledge, but also become familiar with the future of smart cities. This way, when children encounter technology, they will already be prepared and able to deal with technological advances that will shape the future scenario.